John Woman - Mosley, Walter (Grove Press, 2018)
At twelve years old, Cornelius, the son of an Italian-American woman and an older black man from Mississippi named Herman, secretly takes over his father's job at a silent film theater in New York's East Village. Five years later, as Herman lives out his last days, he shares his wisdom with his son, explaining that the person who controls the narrative of history controls their own fate. After his father dies and his mother disappears, Cornelius sets about reinventing himself--as Professor John Woman, a man who will spread Herman's teachings into the classrooms of his unorthodox southwestern university and beyond. But there are other individuals who are attempting to influence the narrative of John Woman, and who might know something about the facts of his hidden past.